2018
DOI: 10.1111/jac.12268
|View full text |Cite
|
Sign up to set email alerts
|

Soil urease and catalase responses to ozone pollution are affected by the ozone sensitivity of wheat cultivars

Abstract: Understanding the effects of elevated O3 (EO3) on belowground process such as soil enzyme activities is essential to evaluate plant physiological reaction and soil processes (e.g. carbon and nitrogen turnover) under predicted increases in atmospheric O3. In this study, O3‐induced changes in soil urease (UA) and catalase activities (CTA) under two contrasting wheat cultivars (O3‐sensitive versus O3‐tolerant) were investigated using a free‐air O3 enrichment (O3FACE) facility in China. EO3 (60 ppb compared with 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Soil enzymatic activity is regarded as a crucial indicator of soil quality and agroecological stability ( Acosta-Martinez et al, 2018 ). Sucrase catalyzes the hydrolysis of sucrose to produce fructose and glucose ( Frankeberger and Johanson, 1983 ), while catalase catalyzes the decomposition of H 2 O 2 into O 2 and H 2 O ( Kou et al, 2018 ). Here, soil sucrase and catalase activity exhibited a remarkable decrease in the HD site compared with the ND site of konjac.…”
Section: Discussionmentioning
confidence: 99%
“…Soil enzymatic activity is regarded as a crucial indicator of soil quality and agroecological stability ( Acosta-Martinez et al, 2018 ). Sucrase catalyzes the hydrolysis of sucrose to produce fructose and glucose ( Frankeberger and Johanson, 1983 ), while catalase catalyzes the decomposition of H 2 O 2 into O 2 and H 2 O ( Kou et al, 2018 ). Here, soil sucrase and catalase activity exhibited a remarkable decrease in the HD site compared with the ND site of konjac.…”
Section: Discussionmentioning
confidence: 99%
“…From June to August 2016, ozone replaced PM 10 and PM 2.5 as the primary pollutant in the three urban agglomerations of Beijing-Tianjin-Hebei, Yangtze River Delta, and Pearl River Delta in China [3]. Many studies have found that near-surface O 3 could destroy photosynthetic pigments and damage chloroplasts in plants [4,5], change carbon metabolism [6,7], affect enzyme activities [8,9] and microbial communities [10,11], which might reduce production of crops and trees, and even lead to the degradation of forest ecosystem [12].…”
Section: Introductionmentioning
confidence: 99%